WebAssembly in action : with examples using C++ and Emscripten - Gallant, Gerard (Manning Publications Co., 2019)
WebAssembly in Action teaches you how to write and run high-performance browser-based applications using C++ and other languages supported by WebAssembly. In it, you'll learn to create native WebAssembly modules, interact with JavaScript components, and maximize performance with web workers and pthreads. And you'll love how the clearly organized sections make it a breeze to find the important details about every function, feature, and technique.